ASSOCIATION OF LOKAN SHELL Geloina erosa, SOLANDER 1786 AND MANGROVE AT KAHYAPU COASTAL AREA OF ENGGANO ISLAND, BENGKULU PROVINCE - Nella Tri Agustini; Dietriech G. Bengen; Tri Prartono (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Lokan shell Geloina erosa closely related to mangrove ecosystem in Enggano island. Mangrove is one supplier of organic materials required by Lokan shell. The research conducted in September 2015 - January 2016 at mangrove ecosystems in Kahyapu coastal area, aims to analyse lokan shells Geloina erosa conditions and its association with mangrove ecosystems. Sampling of mangrove vegetation was taken using line transect and lokan shell sampling using plot in mangrove ecosystem. The results show that mangrove condition of the Kahyapu coastal area was in healthy condition for the growth of lokan shell. Lokan shell are significantly assosiated with mangrove in Kahyapu coastal area of Enggano Island.